Audit Teknologi Informasi Bandung Techno Park Menggunakan Framework Cobit 5 Pada Domain EDM (Evaluate, Direct, And Monitor) - Daniel Alexander Octavianus Turang; Delphine Yusticia Ratnasari; Ike Yunia Pasa (INTEK : Jurnal Informatika dan Teknologi Informasi, 2018)
IT governance is needed as a guide to be used in the setting of the utilization of information technology in an organization. IT governance in organizations provides IT solutions that will be used to handle with related problems in organization, handle risks and also reduce operational costs. The research process design was conducted on COBIT 5, that is in the EDM domain (Evaluate, Direct, and Monitor) which focuses on on ensuring the achievement of organizational goals by governance framework setting and maintenance, ensure benefit delivery, risk optimisation, resource optimisation, and stakeholder transparacy. The results of the maturity level at level 1 for the EDM05 processes, level 2 for the EDM03 processes, while the EDM01, EDM02 and EDM01 processes were at level 3. The target set was level 4, where where the management of supervise and measure of things that have been met with the procedures, as well as taking action when the process does not run effectively.